UNIVERSITY IN «KNOWLEDGE SOCIETY» УНИВЕРСИТЕТ В «ОБЩЕСТВЕ ЗНАНИЙ» УНІВЕРСИТЕТ У «СУСПІЛЬСТВІ ЗНАНЬ» - N. P. Ragozin (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The article studies peculiarities of development of modern university system of production and spreading of knowledge. There is given comparative analysis of historic types of university:
prior to classical (Medieval Ages), classical ‘Gumboltd’s’ (New Age) and post classical university (XX – early XXI century). There is enlightened a tendency to bifurcation of post classical
university into mass and elite university with a perspective of turning both of them into a capitalistic enterprise. Рассматриваются особенности развития современной университетской системы производства и распространения знания. Даётся сравнительный анализ исторических
типов университета: доклассического (эпоха Средневековья), классического «гумбольдтовского» (Новое время) и постклассического университета (XX – начало XXI века). Прослеживается тенденция раздвоения постклассического университета на массовый и элитарный университеты с перспективой превращения обоих в капиталистическое предприятие. Розглядаються особливості розвитку університетської системи виробництва і розповсюдження знання. Дається порівняльний аналіз історичних типів університету: докласичного (епоха Середньовіччя), класичного «гумбольдтівського» університету (Новий час) і посткласичного університету (ХХ-ХХІ століття). Досліджується тенденція роздвоєння посткласичного університету на масовий і елітарний університети з перспективою перетворення обох у капіталістичне підприємство.